Potential of gastronomy tourism from traditional culinary in Sikka Regency, East Nusa Tenggara - Rosalina Andriyani Ebang Pareira; Aurelius Fredimento; Agung Yuliyanto Nugroho (Journal of Rural Tourism, 2024)
Purpose - The purpose of this research is to understand the philosophy, historical tradition, and social aspects of Lekun in Sikka Regency, as well as its role as a gastronomic tourist attraction. It also aims to explore the standard recipe for making and serving Lekun and the government's preservation efforts.Methodology/Design/Approach - The research uses a descriptive qualitative approach, with data collected through interviews, observations, literature reviews, and documentation to gather insights on the tradition, preparation, and potential for tourism. Finding - The findings of the study reveal several important insights about Lekun in Sikka Regency. First, it was discovered that Lekun holds significant cultural value, deeply tied to the traditions, philosophy, and social practices of the Sikka Krowe ethnic group. It is not merely a traditional snack but also plays a vital role in ceremonial events, particularly weddings. The process of making Lekun is also crucial, as it ensures the preservation of its authentic preparation and presentation.Originality/Value - This research emphasizes the importance of preserving traditional food like Lekun for cultural heritage and tourism. It highlights the need for government support in both education and business development to maintain and promote Lekun as a gastronomic tourist attraction in Sikka Regency.